2003
DOI: 10.1203/01.pdr.0000042443.65546.e1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Smoking on Fetal Catecholamine Concentrations at Birth

Abstract: The aim of this study was to compare catecholamine concentrations in the fetal umbilical artery cord blood from the offspring of smokers versus the offspring of nonsmokers. Pregnant women who were self-identified as smokers (Ն10 cigarettes per day throughout pregnancy) or nonsmokers were recruited for study participation. Maternal blood was collected for cotinine concentrations. Umbilical artery cord blood was collected at delivery for arterial pH and catecholamine concentrations. Cord blood was obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…In addition to myelination, FA increases reflect maturational increases in cell packing density, fiber diameter, and directional coherence (Beaulieu and Allen, 1994;Shimony et al, 1999;Beaulieu, 2002). Thus, observed group differences are consistent with previous evidence that stimulation of nAChRs by nicotine may disrupt neurodevelopment by disrupting the trophic actions of acetylcholine (Slotkin, 1998;Oncken et al, 2003). FA increases were most extensive in adolescent smokers with and without prenatal exposure.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to myelination, FA increases reflect maturational increases in cell packing density, fiber diameter, and directional coherence (Beaulieu and Allen, 1994;Shimony et al, 1999;Beaulieu, 2002). Thus, observed group differences are consistent with previous evidence that stimulation of nAChRs by nicotine may disrupt neurodevelopment by disrupting the trophic actions of acetylcholine (Slotkin, 1998;Oncken et al, 2003). FA increases were most extensive in adolescent smokers with and without prenatal exposure.…”
Section: Discussionsupporting
confidence: 87%
“…For example, several studies have shown lower autonomic arousal and vigilance levels in children of mothers who smoked during pregnancy (Horne, Franco, Adamson, Groswasser, & Kahn, 2004;Kristjansson et al, 1989;Raine, 2002). Measures of arousal and vigilance might be specifically sensitive to prenatal smoking, because without continued nicotinic intake after birth, the increased number of nicotinic cholinergic receptor binding sites that have been formed as a consequence of in utero-nicotine exposure may be understimulated (Oncken et al, 2003;Raine, 2002;Slotkin et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Significantly lowered levels of catecholamines found in umbilical cord blood in response to hypoxemia during parturition may explain the increased perinatal morbidity and mortality associated with smoking during pregnancy (Oncken et al, 2002). A blunted catecholamine response to hypoxic stress with a greater risk of death to offspring was also observed in rats receiving nicotine throughout gestation.…”
Section: Nicotine In Pregnancy and Childhoodmentioning
confidence: 95%